2002
DOI: 10.1152/ajpheart.00187.2002
|View full text |Cite
|
Sign up to set email alerts
|

A new inbred Wistar-Kyoto rat substrain exhibiting apparent salt sensitivity and borderline hypertension

Abstract: Alemayehu, Adamu, Laura Breen, and Morton P. Printz. A new inbred Wistar-Kyoto rat substrain exhibiting apparent salt sensitivity and borderline hypertension. Am J Physiol Heart Circ Physiol 283: H1181-H1190, 2002. First published May 23, 2002 10.1152/ajpheart.00187.2002The normotensive Wistar-Kyoto (WKY) rat strain is a traditional control for the spontaneously hypertensive rat (SHR). We found trait differences between two inbred normotensive WKY strains, derived originally from different vendors, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…24 We observed spontaneous BK current events in myocytes isolated from SD, WKY, and SHR arteries held at a membrane potential of Ϫ40 mV ( Figure 1A). Although the frequency of these events was comparable at approximately 4 Hz ( Figure 1B; PϾ0.05), BK current amplitudes were about 50% smaller in SHR than in SD myocytes (PϽ0.05, nϭ700 events from 5 myocytes).…”
Section: Bk Currents But Not Ca 2؉ Sparks Are Smaller In Borderlinementioning
confidence: 94%
See 1 more Smart Citation
“…24 We observed spontaneous BK current events in myocytes isolated from SD, WKY, and SHR arteries held at a membrane potential of Ϫ40 mV ( Figure 1A). Although the frequency of these events was comparable at approximately 4 Hz ( Figure 1B; PϾ0.05), BK current amplitudes were about 50% smaller in SHR than in SD myocytes (PϽ0.05, nϭ700 events from 5 myocytes).…”
Section: Bk Currents But Not Ca 2؉ Sparks Are Smaller In Borderlinementioning
confidence: 94%
“…The systolic blood pressure of SD and SHR rats used in this study was 117Ϯ3 and 195Ϯ5 mm Hg, respectively, as determined by tail-cuff plethysmography. We also examined a putative "borderline hypertensive" WKY rat substrain 24 to determine if there is a relationship between BK channel function and the severity of hypertension. The systolic blood pressure of our WKY rats was 135Ϯ3 mm Hg.…”
Section: Bk Currents But Not Ca 2؉ Sparks Are Smaller In Borderlinementioning
confidence: 99%
“…The susceptibility of different substrains to dietary sodium manipulation may be tied to differences in the expression of receptors, such as the tachykinins, in brain regions that mediate the psychomotor stimulant and reinforcing properties of amphetamine and sodium solutions (27,32). These results add to the literature identifying strain differences in salt intake, responses to stress, and psychomotor stimulant sensitivity (2,5,35,43,54).…”
Section: Discussionmentioning
confidence: 67%
“…In this vein, it is not clear why the authors chose SD rats over other strains of WKY that have been shown to be normotensive and salt resistant, such as WKY/ lj-cr, having a similar SBP (Ϸ118 mm Hg) to SD themselves. 9 small cumulative effect on BP.…”
Section: Ion Channel Dysfunction In Genetic Hypertensionmentioning
confidence: 98%
“…Recent studies suggest that WKY, because of random breeding with certain suppliers, exist as different genetic strains, with some having borderline hypertension and high salt sensitivity (WKY/lj-tf). 9 SHR develop hypertension within 6 weeks of age and is fully established by 12 to 16 weeks. Using these SHR models, numerous patch-clamp studies have reported increased amplitude of currents through VDCCs in several vascular beds, including the cerebral circulation, resulting from both upregulation of the channel and membrane depolarization (see Reference 3).…”
Section: Ion Channel Dysfunction In Genetic Hypertensionmentioning
confidence: 99%